Implementasi Program Akselerasi Kitab Kuning dalam Menunjang Kualitas Siswa di Madrasah Tsanawiyah Darul Lugah Wal Karomah Sidomukti Kraksaan Probolinggo - Nur Hayati (Lembaga Pengembangan Kinerja Dosen, 2023)
The focus of research which became the main study in this study was about the acceleration program to read the yellow book in Islamic Boarding Schools. The learning acceleration program is a program to improve the quality of learning for students, especially students who live in Islamic boarding schools. In this study, researchers want to explain two topics regarding the acceleration of reading the yellow book in Islamic boarding schools and the quality of students with the acceleration program and focused on students at the Tasanawiyah Madrasah level. The existence of an acceleration program aims to increase the causality and validity of student learning in working on the yellow book which is the main material of teaching. This research uses a qualitative approach, with data collection techniques are interviews, conservation and documentation. Data analysis techniques that researchers use is data reduction, data presentation and conclusions. The result of this research was that Santri, who was initially somewhat difficult to learn and understand the book of Turats, became easier to understand. Thus, in accordance with the target set by the pesantren within two years, students can graduate and move to a more challenging level, namely the Takhassus program.